The Effect of Shareholder Pressure, Profitability, Leverage and Company Size on the Sustainability Report Quality - Putu Dias Listya Dewi; Gerianta Wirawan Yasa (Dinasti Publisher, 2025)
This study was conducted to examine the effect of shareholder pressure, profitability, leverage, and company size on the sustainability report quality. The population in this study are banking companies listed on the Indonesia Stock Exchange for the period 2021-2023. The sampling technique used was purposive sampling, which resulted in 27 companies as samples with a total of 77 observation data. Data analysis was carried out using the multiple linear regression method. The results showed that shareholder pressure and profitability have no effect on the sustainability report quality. Leverage and company size have a positive effect on the sustainability report quality.